2021
DOI: 10.3390/ani11030764
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Polyamine Precursors, Polyamines, and Steroid Hormones on Temporal Messenger RNA Abundance in Bovine Satellite Cells Induced to Differentiate

Abstract: Emerging research suggests that hormones found in anabolic implants interact with polyamine biosynthesis. The objective of this study was to determine the effects of steroidal hormones, polyamines and polyamine precursors on bovine satellite cell (BSC) differentiation and polyamine biosynthesis temporally. Primary BSCs were induced to differentiate in 3% horse serum (CON) and treated with 10 nM trenbolone acetate (TBA), 10 nM estradiol (E2), 10 nM TBA and 10 nM E2, 10 mM methionine, 8 mM ornithine, 2 mM putres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Implants have the added benefit of also increasing both the environmental sustainability of the industry [2] and economic return to producers [15]. However, despite the clear benefits of implanting, the exact physiological and molecular mechanism that anabolic implants operate through to increase overall growth and efficiency remains elusive [9,12]. Furthermore, when trace minerals are supplemented at higher concentrations recommended by feedlot consultants, rather than national research council recommendations, an increase in growth is observed [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implants have the added benefit of also increasing both the environmental sustainability of the industry [2] and economic return to producers [15]. However, despite the clear benefits of implanting, the exact physiological and molecular mechanism that anabolic implants operate through to increase overall growth and efficiency remains elusive [9,12]. Furthermore, when trace minerals are supplemented at higher concentrations recommended by feedlot consultants, rather than national research council recommendations, an increase in growth is observed [13].…”
Section: Discussionmentioning
confidence: 99%
“…Anabolic implants increase economically viable traits such as average daily gain (ADG), feed intake, feed efficiency (FE), hot carcass weight (HCW), and ribeye area (REA) [4,7]. However, the exact physiological and molecular mechanisms by which anabolic implants operate to increase skeletal muscle growth in cattle remains elusive [9][10][11][12]. Furthermore, the increase in growth caused by anabolic implants, may increase trace mineral requirements to support skeletal muscle growth [13], as lambs implanted with zeranol tended to retain greater amounts of Zn, and lose less Cu and Mn in feces and urine [14].…”
Section: Introductionmentioning
confidence: 99%
“…Control cultures received just SFM. The treatment concentrations used in the analysis of protein synthesis were selected based upon results from past studies completed by our laboratory that impacted the growth of bovine satellite cells [ 22 , 31 ]. Additionally, in the protein synthesis study, which was completed after the proliferation study, the E2 and TBA + E2 treatments were added because further review of past literature demonstrated evidence for a potential interaction between E2 and polyamine biosynthesis [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cell lysate was collected at three different time points for analysis relative to proliferation (0.5, 12 and 24 h post-treatment) or protein synthesis (1, 12, and 24 h post-treatment). These time points were based off of previous work completed by our research group that demonstrated changes in gene expression in bovine satellite cells [ 22 , 31 ]. In addition, these specific time points were chosen because changes in gene expression are likely to be observed prior to a gross change in proliferation or protein synthesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation